2019
DOI: 10.1002/ejic.201801206
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium(II) Aqua Complex as Efficient Chemical and Photochemical Catalyst for Alkene and Alcohol Oxidation

Abstract: Different synthetic routes have been developed to obtain the aqua complex trans‐[RuII(trpy)(pypz‐H)(OH2)](PF6)2, Ru6. This complex, together with the chlorido intermediate complexes cis‐ and trans‐[RuIICl(pypz‐H)(trpy)]+, Ru5a and Ru5b, have been fully characterized by analytical, spectroscopic, and electrochemical methods. Furthermore, the trans‐Ru5b complex has been characterized in the solid state through single‐crystal X‐ray diffraction analysis. The aqua complex Ru6 was tested as catalyst in the photooxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The sixth coordination site is occupied by the monodentate acetonitrile ligand. All bond distances and angles are within the expected values for these types of complexes. For instance, it is interesting to note that the Ru–N2 bond length in the bpy ligand, where the N2 atom is placed trans to the pyridyl N4 atom of trpy, is longer (2.069 Å) than the analogous distance Ru–N1 (2.033 Å), where the N1 atom is trans to the N6 atom of the acetonitrile ligand. This evidence highlights the stronger trans influence of the pyridine ring with respect to the acetonitrile ligand.…”
Section: Results and Discussionsupporting
confidence: 56%
“…The sixth coordination site is occupied by the monodentate acetonitrile ligand. All bond distances and angles are within the expected values for these types of complexes. For instance, it is interesting to note that the Ru–N2 bond length in the bpy ligand, where the N2 atom is placed trans to the pyridyl N4 atom of trpy, is longer (2.069 Å) than the analogous distance Ru–N1 (2.033 Å), where the N1 atom is trans to the N6 atom of the acetonitrile ligand. This evidence highlights the stronger trans influence of the pyridine ring with respect to the acetonitrile ligand.…”
Section: Results and Discussionsupporting
confidence: 56%
“…Styrene epoxide belongs to an important class of compounds that are useful in the synthesis of a wide range of materials, including epoxy resins, perfumes and fine chemicals. 1 Many works have recently reported on styrene oxidation, [2][3][4][5][6][7] such as that over heterogeneous cobalt, 8 manganese, 9 gold, 10 titanium, 11,12 silver, 13,14 iron, 15,16 palladium, 17 copper, 18 and ruthenium. 19 However, most of these catalytic systems mainly contain metalloporphyrin derivatives imitating cytochrome P450 enzymes and these catalytic systems require high temperature, high O 2 pressure, or the addition of a noble metal cocatalyst or sacrificial agent.…”
Section: Introductionmentioning
confidence: 99%
“…The iron(III) complex with a tertraamido macrocyclic ligand showed an autocatalytic reaction mechanism for the selective catalytic oxidation of cyclohexane without a generation of free radical mechanism. Recently, Manrique et al 21 reported a new aqua complex trans-[Ru II (trpy)(pypz-H)(OH 2 )](PF 6 ) 2 , as a catalyst in the photocatalytic oxidation of alkenes like 1-octene and styrene, and it exhibited conversions > 50 %. The [Ru v =O] 2+ acted as an active species in the complex which showed moderate to high conversions and good selectivity values for the epoxides.…”
Section: Introductionmentioning
confidence: 99%